2019
DOI: 10.1111/apt.15169
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: gabapentin vs baclofen in the treatment of suspected refractory gastro‐oesophageal reflux‐induced chronic cough

Abstract: Background: Neuromodulators are considered potential therapeutic options for refractory gastro-oesophageal reflux-induced chronic cough. Aim: To compare the efficacy of gabapentin and baclofen in patients with suspected refractory gastro-oesophageal reflux-induced chronic cough. Methods: Two hundred and thirty-four patients with suspected refractory gastrooesophageal reflux-induced chronic cough, who failed an 8-week course of omeprazole and domperidone, were recruited into the open-labelled study and randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 34 publications
4
81
0
Order By: Relevance
“…According to a gradual dose escalation schedule 8 , gabapentin (Hengrui Pharmaceutical Co., Ltd., Jiangsu, China) was given with a starting dose of 100 mg, three times daily, then increased by 100 mg each time every 3 days, until a maximum dose of 900 mg daily (300 mg, three times) was reached or the side effects became intolerant. The treatment was maintained for 8 weeks in patients with a favorable response but discontinued at the end of week 4 for patients unresponsive to gabapentin.…”
Section: Gabapentin Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a gradual dose escalation schedule 8 , gabapentin (Hengrui Pharmaceutical Co., Ltd., Jiangsu, China) was given with a starting dose of 100 mg, three times daily, then increased by 100 mg each time every 3 days, until a maximum dose of 900 mg daily (300 mg, three times) was reached or the side effects became intolerant. The treatment was maintained for 8 weeks in patients with a favorable response but discontinued at the end of week 4 for patients unresponsive to gabapentin.…”
Section: Gabapentin Treatmentmentioning
confidence: 99%
“…Recently, gabapentin has well been demonstrated for its antitussive effectiveness in patients with CRC 5 and has become a recommended therapy in the latest ACCP and ERS cough guidelines 2,6 . However, its therapeutic e cacy is suboptimal since approximately 40% of patients fail to gabapentin treatment 7,8 . Therefore, it is imperative to screen patients most likely responsive to gabapentin therapy to improve the success rate and avoid potential adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The authors’ declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementsmentioning
confidence: 99%
“…We thank Drs Naik and Vaezi for their insightful comments regarding our recently published article . The purpose of our study was to compare the efficacy of gabapentin and baclofen as add‐on therapy for the management of suspected refractory gastro‐oesophageal reflux‐induced chronic cough.…”
mentioning
confidence: 99%
“…In their open‐label, single centre, randomised controlled trial comparing the efficacy of baclofen versus gabapentin for suspected reflux‐related cough, Dong et al showed similar rates of improvement in subjective cough symptoms (57.3% vs 53.0%) . This study has highlighted an important and challenging topic often faced in clinical practice of patients with persistent cough.…”
mentioning
confidence: 99%